Chronic Disease Registries – Trends and Challenges - Schüz, Joachim; Fored, Michael (Methods of Information in Medicine, 2017)
Background: This accompanying editorial is an introduction to the focus theme of “chronic disease registries - trends and challenges”.Methods: A call for papers was announced on the website of Methods of Information in Medicine in April 2016 with submission deadline in September 2016. A peer review process was established to select the papers for the focus theme, managed by two guest editors.Results: Three papers were selected to be included in the focus theme. Topics range from contributions to patient care through implementation of clinical decision support functionality in clinical registries; analysing similar-purposed acute coronary syndrome registries of two countries and their registry-to- SNOMED CT maps; and data extraction for speciality population registries from electronic health record data rather than manual abstraction.Conclusions: The focus theme gives insight into new developments related to disease registration. This applies to technical challenges such as data linkage and data as well as data structure abstraction, but also the utilisation for clinical decision making.
Keywords: Registries; health information; electronic health records; clinical decision support